2022
DOI: 10.3389/fendo.2022.962635
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the efficacy and signaling pathways activated by stem cell-derived extracellular vesicles in diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is one of complications of diabetes mellitus with severe microvascular lesion and the most common cause of end-stage chronic kidney disease (ESRD). Controlling serum glucose remains the primary approach to preventing and slowing the progression of DKD. Despite considerable efforts to control diabetes, people with diabetes develop not only DKD but also ESRD. The pathogenesis of DKD is very complex, and current studies indicate that mesenchymal stromal cells (MSCs) regulate complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The contents of these cargoes serve a useful purpose. It was shown that stem cell exos protect the kidney from damage through multiple pathways by eliciting anti-apoptotic, anti-inflammatory, anti-oxidative, and anti-fibrotic effects and by regulating podocyte autophagy ( 230 ). Therefore, MSCExos are expected to be a potential therapeutic option for the treatment of DKD ( 231 ).…”
Section: Treatmentmentioning
confidence: 99%
“…The contents of these cargoes serve a useful purpose. It was shown that stem cell exos protect the kidney from damage through multiple pathways by eliciting anti-apoptotic, anti-inflammatory, anti-oxidative, and anti-fibrotic effects and by regulating podocyte autophagy ( 230 ). Therefore, MSCExos are expected to be a potential therapeutic option for the treatment of DKD ( 231 ).…”
Section: Treatmentmentioning
confidence: 99%
“…UC-MSCs improve oxidative damage and apoptosis in the kidneys of DN rats. UC-MSCs can activate the PI3K/Akt signaling pathway, causing nuclear factor erythroid 2-related factor 2 (Nrf2) to translocate to the nucleus and promote downstream factor expression, which in turn inhibits proapoptotic proteins such as Bax and caspase3 and upregulates heme oxygenase-1 (HO-1) and superoxide dismutase 2 (SOD2) levels [ 44 ]. However, the specific way in which UC-MSCs affect the PI3K/Akt signaling pathway was not demonstrated.…”
Section: Studies On the Mechanism Of Mscs For The Treatment Of Dm And...mentioning
confidence: 99%
“…In addition to possess the function of MSCs, the adverse reactions of MSCs can be avoided to a certain extent by their extracellular vesicles (EVs), including exosomes with a diameter of 30–120 nm, and micro-vesicles ranging from 100 nm to 1 μm in size. Mounting evidence supports that MSCs released vesicles (MSCs-EVs), which may have greater clinical application potential than that of MSCs [ 14 ]. In recent years, MSC-Exo is becoming a novel and promising cell-free therapeutic agent in many ongoing clinical studies Several clinical research revealed that MSC-Exos could against different diseases, including kidney diseases, osteoarthritis, stroke, Alzheimer’s disease and type 1 diabetes [ 15–18 ].…”
Section: Introductionmentioning
confidence: 99%